SCIENTIFIC INTERPRETATION OF RAKHIM AKHMEDOV'S WORK IN COLOR ART OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
Rahim Ahmedov Ahmedovich (July 26, 1921 - 2008, Tashkent) was born in Tashkent. From 1937 to 1941 he studied at the Tashkent Art School under Hikmat Rakhmonov and Malik Nabiyev. During the war, he served in the military on the North Caucasus front and participated in propaganda work. After the war he returned to Tashkent and continued his studies at the Art School, from where he was sent in 1947 to Leningrad (now St. Petersburg) to study at the I. Repin Institute of Art, Sculpture and Architecture. I.A.Serebryanniy, A.A. He graduated from the institute in 1953 with a diploma in "People's Guard" after studying under leading Russian artists such as Milnikov and Yu.N. Neprinsev.